2018
DOI: 10.1002/imhj.21708
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Adaptations of Evidence‐based Home‐visitation Models in Tribal Communities

Abstract: The Tribal Maternal, Infant, and Early Childhood Home Visiting (Tribal MIECHV) Program provides federal grants to tribes, tribal consortia, tribal organizations, and urban Indian organizations to implement evidence-based home-visiting services for American Indian and Alaska Native (AI/AN) families. To date, only one evidence-based home-visiting program has been developed for use in AI/AN communities. The purpose of this article is to describe the steps that four Tribal MIECHV Programs took to assess community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(67 citation statements)
references
References 30 publications
1
66
0
Order By: Relevance
“…We were able to conduct a particularly in-depth exploration of our efforts to balance community needs with scientific rigor. Our work resembles what Hiratsuka et al (2018) found in their review of adaptations made to four home visiting models within tribal communities. In both cases, our work and Hiratsuka et al, deep structural adaptations included community engagement and hiring of community members to deliver the program as well as the development of new handouts, content or activities, and changes to delivery and training.…”
Section: Lessons Learnedsupporting
confidence: 70%
See 2 more Smart Citations
“…We were able to conduct a particularly in-depth exploration of our efforts to balance community needs with scientific rigor. Our work resembles what Hiratsuka et al (2018) found in their review of adaptations made to four home visiting models within tribal communities. In both cases, our work and Hiratsuka et al, deep structural adaptations included community engagement and hiring of community members to deliver the program as well as the development of new handouts, content or activities, and changes to delivery and training.…”
Section: Lessons Learnedsupporting
confidence: 70%
“…We frame our adaptations using the approach proposed by Resnicow et al (1999) and recently applied to evaluations of home visiting programs adapted to tribal settings in the MIECHV program by Hiratsuka et al (2018). Hiratsuka et al reviewed four home visiting programs adapted within tribal communities.…”
Section: Adapting Home Visiting Programs Within American Indian Commumentioning
confidence: 99%
See 1 more Smart Citation
“…SCF has extensive experience in tailoring clinical and research processes, and the language used to describe them, to the needs and preferences of its patient population ( Driscoll et al, 2013 ; Starks et al, 2015 ; Hiratsuka et al, 2017a , b , 2018c , 2019a , b ; Muller et al, 2017 ; Dillard et al, 2018 ). For example, considerable organizational resources are devoted to training clinicians and staffin the use of a “shared language” that encourages rapport among employees and between providers and patients and was referred to by participants ( Eby, 2007 ; Gottlieb, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…These standards echo the principle-based approach to communicating about precision medicine described by participants, and suggests that patients, providers, and leaders have internalized these concepts and come to expect their application in patient engagement. In addition, major research streams at SCF concern the exploration of community preferences regarding dissemination of research results and involve tailoring interventions developed for use in other populations to meet the needs, expectations, and preferences of patients ( Starks et al, 2015 ; Hiratsuka et al, 2017a , 2018a , b , c , 2019b ; Muller et al, 2017 ; Beans et al, 2018 ; Shane et al, 2018 ). Any effort to communicate about precision medicine at SCF will benefit from this organizational commitment to and competency in tailoring clinical and research practices to patient needs.…”
Section: Discussionmentioning
confidence: 99%